Changes in limiting resources determine spatio-temporal variability in tree–grass interactions - Gea-Izquierdo, G.; Montero, G.; Cañellas, I. (Agroforestry Systems, 2009)
Changing biotic and abiotic stress mediate in plant–plant interactions resulting in positive to neutral or negative effects, and these effects can change with gradients of stress or through plant dynamics. Here we studied the variability in annual grass production and composition induced by gradients of intercepted light by trees in years of contrasting precipitation in Mediterranean holm oak open woodlands. Although trees reduce the light radiance received by the pasture community, the presence of trees generally had a positive effect on pasture production in average climatic years where soil fertility was low. However, the interaction changed with increasing abiotic water stress. In a dry year, the increase in fertility could not be utilized and the effect of the crown was neutral. The effect of shade turned out to be beneﬁcial for growth, contrary to the situation in an average climatic year. Light insolation was positive for legume biomass. There was high variability in functional components over the course of the growing period and from 1 year to another. Under low levels of other biotic stresses such as livestock grazing or root competition, the limiting factor among light, soil moisture or soil nutrients may determine whether facilitation or competition occurs.
Keywords: Abiotic stress; competition; Dehesa; Facilitation; Grass production; Mediterranean

Changes in limiting resources determine spatio-temporal variability in tree–grass interactions - Gea-Izquierdo, G; Montero, G; Cañellas, I (Agroforestry Systems, 2009)
Changing biotic and abiotic stress mediate in plant–plant interactions resulting in positive to neutral or negative effects, and these effects can change with gradients of stress or through plant dynamics. Here we studied the variability in annual grass production and composition induced by gradients of intercepted light by trees in years of contrasting precipitation in Mediterranean holm oak open woodlands. Although trees reduce the light radiance received by the pasture community, the presence of trees generally had a positive effect on pasture production in average climatic years where soil fertility was low. However, the interaction changed with increasing abiotic water stress. In a dry year, the increase in fertility could not be utilized and the effect of the crown was neutral. The effect of shade turned out to be beneﬁcial for growth, contrary to the situation in an average climatic year. Light insolation was positive for legume biomass. There was high variability in functional components over the course of the growing period and from 1 year to another. Under low levels of other biotic stresses such as livestock grazing or root competition, the limiting factor among light, soil moisture or soil nutrients may determine whether facilitation or competition occurs.
Keywords: Abiotic stress; competition; Dehesa; Facilitation; Grass production; Mediterranean